PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DI SMP NEGERI 13 PEKANBARU - Sinaga, Desinawati; Gimin, Gimin; Sumarno, Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research aims to examine the influence of Problem Based Learning model on social studies learning outcomes in State Junior High School 13 Pekanbaru Academic Year 2018/2019. This study uses quasi-experimental methods (quasi experiment). The population of this study was the seventh grade students of Pekanbaru State Junior High School 13 which consisted of ten classes with a total of 277 students. The number of samples of this study is one class, namely class VII 2 as many as 31 students obtained by class sample techniques. Data collection uses observation, tests and documentation. The data analysis used is the Paired Samples Test. The results of data analysis showed that there were significant differences in the average value of the class given the treatment of the Problem Based Learning model and the class given the lecture method treatment, where the experimental class was higher than the control class. So that it can be concluded the learning process by using the Problem Based Learning model influences student learning outcomes on social studies subjects. In this study there are several suggestions put forward by the researcher, namely to the teacher that the teacher should multiply the variety of learning models used, so that it fits between the learning model and the subject matter. To Researchers Furthermore, research using Problem Based Learning learning models for other researchers is expected to examine students' interest in learning or motivation in learning by using the learning model.Key Words: Problem based learning, learning outcomes, social studies at junior high school